ASAP3 - New Data Taking and Analysis Infrastructure for PETRA III. Issue 4 (December 2015) - Strutz, M; Gasthuber, M; Aplin, S; Dietrich, S; Kuhn, M; Ensslin, U; Smirnov, G; Lewendel, B; Guelzow, V
Abstract: Data taking and analysis infrastructures in HEP (High Energy Physics) have evolved during many years to a well known problem domain. In contrast to HEP, third generation synchrotron light sources, existing and upcoming free electron lasers are confronted with an explosion in data rates driven primarily by recent developments in 2D pixel array detectors. The next generation of detectors will produce data in the region upwards of 50 Gbytes per second. At synchrotrons, data was traditionally taken away by users following data taking using portable media. This will clearly not scale at all. We present first experiences of our new architecture and underlying services based on results taken from the resumption of data taking in April 2015. Technology choices were undertaking over a period of twelve month. The work involved a close collaboration between central IT, beamline controls, and beamline support staff. In addition a cooperation was established between DESY IT and IBM to include industrial research and development experience and skills. Our approach integrates HPC technologies for storage systems and protocols. In particular, our solution uses a single file-system instance with a multiple protocol access, while operating within a single namespace.